Understanding Household Cooked Rice Waste: A Comparative Study between Rural and Urban Areas in Pasuruan, Indonesia - Wenny Mamilianti; Yuyun Maslakha (Universitas Muhammadiyah Malang, 2024)
Household food consumption patterns exhibit variability, with households serving as prominent contributors to food waste generation, thereby leading to adverse economic ramifications. This study aims to calculate the amount of household cooked rice waste, calculate the economic value loss from household cooked rice waste, and analyze the factors that influence household cooked rice waste in rural and urban areas. The investigation was carried out in two distinct locales: Purwo, Sekarmojo, Purwosari, Pasuruan (representing rural areas) and Sebani, Gadingrejo, Pasuruan (representing urban areas). The weight of household cooked rice waste is computed utilizing the fDMM (Faktor Dalam Masak Mentah or Factor in Raw Food Cooking) methodology. Economic loss incurred due to household cooked rice waste is estimated by multiplying the prevailing rice price by the converted volume of rice waste. Multiple regression analysis is employed to discern the contributing factors to household cooked rice waste. Findings indicate a higher incidence of household cooked rice waste in rural settings compared to urban counterparts, consequently resulting in greater economic repercussions. In Sekarmojo, household cooked rice waste is affected by several factors, including the quantity of rice cooked, household income, family size, and frequency of rice consumption. Likewise, in Sebani, household cooked rice waste is affected by variables such as the quantity of rice cooked, household size, frequency of rice consumption, and the utilization of mobile phones for food procurement.